Pengaruh Financial Distress dan Profitabilitas terhadap Konservatisme Akuntansi: Studi Empiris pada Perusahaan Sektor Jasa Transportasi yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Nicola Putri; Fefri Indra Arza; Ahmad Rahbani Sulaiman; Intan Nurbaiti Fawziah (Jurnal Eksplorasi Akuntansi, 2026)
The variables of this study are financial distress and profitability. This research is quantitative and focuses on causal relationships. The study population consists of transportation service sector companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2023. Purposive sampling was conducted to select 72 samples. Multiple regression analysis with SPSS 25 was used. Accounting conservatism was assessed using earnings/accrual measures. The novelty of this study lies in its focus, as it focuses more on conservatism in relation to profit and loss. As a result, researchers include profitability variables, because the level of profitability can influence a company's decision to use conservative accounting methods. The results of the simultaneous testing of the study prove that "independent variables influence the dependent variable" simultaneously. According to the study, "financial distress and profitability variables" negatively affect accounting conservatism.